Analisis Variasi Bahasa Salesman PT Karyatama Maju Berjaya Serta Pemanfaatannya Sebagai Bahan Ajar Teks Negosiasi - Rahmawati, Asmida; Maspuroh, Uah; Syafroni, Roni Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2024)
In carrying out activities as a social creature, it is necessary and can cause language variations. Language variations that have different forms but have forms that resemble language in general. Language variants do not arise as a result of different speakers, but may exist as a result of the emergence of social interactions carried out in various ways. In this research, we examine language variations in terms of formality in the speech of salesmen and buyers in several points in the East Jakarta area with the problem of 1) How do the variations in language used by PT Karyatama salesmen advance successfully to buyers, and 2) What are the results of utilizing the language variations used? by the salesman of PT Karyatama Maju Berjaya to buyers as teaching material for class The theory used is the theory of Martin Joos and Abdul Chaer and Agustina (2010) which relates to language variations in terms of formality. The method used by the author is a descriptive qualitative method and the approach used is a sociolinguistic approach. Based on the research results, it can be concluded as follows: 1) 97 data were found, of which 15 data were in the form of casual variety, 42 data were in the form of familiar variety, and 40 data were in the form of business variety. Meanwhile, for the frozen variety and formal variety, the author did not find this data, and 2) the form of use was in the form of teaching materials in the form of handouts for negotiation text material for class X SMA.